The influence of environmental factors on firm performance with entrepreneurial orientation and manufacturing capability as mediation variables - Rifa Herdianti; Gesit Thabrani (Universitas Negeri Padang, 2023)
This research aims to analyze: (1) the influence of environmental factors on entrepreneurial orientation in SMEs in Padang City (2) the influence of environmental factors on manufacturing capabilities in SMEs in Padang City (3) the influence of entrepreneurial orientation on firms performance in SMEs in Padang City (4) the influence of entrepreneurial orientation on manufacturing capabilities in SMEs in Padang City (5) the effect of manufacturing capabilities on firm performance in SMEs in Padang City (6) the influence of environmental factors on firms’ performance through entrepreneurial orientation in SMEs in Padang City (7) the influence of environmental factors environment on firm performance through manufacturing capabilities in SMEs in Padang City. This research is causal research. The Population of this research is 200 respondents from SMEs actors in the city of Padang who are engaged in manufacturing. The sampling method was using purposive sampling. Collecting data using a questionnaire with a Likert scale. The analysis technique used is smart PLS 4. The results of data processing in the study show that: (1) environmental factors have a significant positive effect on entrepreneurial orientation in SMEs in Padang City (2) environmental factors have a significant positive effect on manufacturing capabilities in SMEs in Padang City (3) entrepreneurial orientation has a significant negative effect on firm performance in SMEs in Padang City (4) manufacturing capability has a significant positive effect on firm performance in SMEs in Padang City (5) entrepreneurial orientation has a significant positive effect on manufacturing capabilities in SMEs in Padang City (6) environmental factors have a significant negative effect on firm performance through entrepreneurial orientation in SMEs in Padang City (7) environmental factors have a significant positive effect on firm performance through manufacturing capabilities in SMEs in Padang City.